PREPARATION OF THE FUTURE TEACHER FOR PEDAGOGICAL CREATIVITY - T.D. Sydorenko (Academy of Cognitive and Natural Sciences, 2008)
In article is revealled possibility of the introducing the new forms o f the work with future teacher, who promoted "saturation" her (its) element creative activity.